Pengaruh Metode Latihan Drill dengan Interval dan Tanpa Interval Terhadap Hasil Pukulan Overhead Clear Forehand Atlet UKM Bulutangkis UPI - Muhammad Hilmi; Ucup Yusup; Muhammad Tafaqur (Jurnal Kepelatihan Olahraga, 2022)
This research is motivated by facts on the ground regarding the training conditions at the UPI Badminton UKM, which tend to pay less attention to training problems and still maintain conventional training, this causes the athletes to have low self-efficacy. This study aims to determine the effect of drill training methods with intervals and without intervals on the results of overhead clear forehand strokes for UPI badminton UKM athletes. The method used in this research is an experimental method using Two Group Pre-test Post-Test Design. Data collection techniques were carried out by giving initial tests to 2 groups. Then given treatment with drill training methods with intervals and without intervals, then a final test was given using the overhead clear forehand test. Data analysis was carried out by using SPSS version 27.00 for Windows. Both of these drill training methods have an effect on the results of overhead clear forehand strokes, but the interval drill method has a more significant effect. So it can be concluded that the drill method with intervals has a more significant effect on the results of overhead clear forehand strokes for UPI Badminton UKM athletes.